BEING A CHURCH IN A SECULARISED WORLD - Mbonu, Caroline (Asian Horizons, 2013)
Undoubtedly, the Second Vatican Council enabled the Church to have a new interpretation of herself for the present era. Not unlike theologians of earlier periods, participants of Vatican II also identified pertinent issues in the life of the Church, issues that form the basis of their deliberations. These early theologians employed every literary form as well as the collective memories of members that were available to them in establishing Christian orthodoxy in the face of a massive secularising influence. Social theorists such as Karl Marx, Sigmund Freud, Max Weber, and Émile Durkheim, all agree that modernization of society would include a decline in the level of religiosity. Pope John XXIII convoked the Council in order to align the Church and her mission with modernity. The metaphor of “Salt of the earth and Light of the world” (Mt 5:13-16) in a sense articulates this mission of being a church in a secularising world.